(untitled) (Applied Biological Research, 2017)
An experiment was conducted at University Research Farm, SKUAST-K, Shalimar, Srinagar (J&K) to evaluate the effect of split application of potassium and nitrogen on their uptake and availability in wheat. The experiment was laid in a split plot design with 15 treatment combinations, viz., 3 levels of potassium (K) @ 30 kg ha-1[K1: 100% K as basal dose – [recommended fertilizer dose (RFP)]; K2: split 50:50; K3: split 25:75] and 5 of nitrogen (N) @ 120 kg ha-1[N1: 50:25:25 (RFP); N2: 25:75, N3: 25:50:25, N4: 50:50 and N5: 0:75:25]. The application of K in equal splits (basal + active tillering) improved grain yield by 10.6 and 11.6%, straw yield by 11.6 and 13.4%, K uptake by 17.2 and 18.8% and N uptake by 16.4 and 17.2% during 2013-14 and 2014-15, respectively, over RFP. The available K decreased steadily with recommended application but maintained its status quo when applied in split dose. The available N in soil maintained status quo with RFP; however, it showed decline when K was applied in splits. The N application in 25:50:25 ratios (basal + active tillering + booting) enhanced grain yield, straw yield and total K and N uptake during both the years. Also, K and N content in soil decreased when N was applied in 3 splits as compared to 2 splits, where it maintained status quo after harvest of 2nd year crop. This indicates there may be need to increase N dose in order to maintain the N status of soil.